Guía docente de estrategias significativas para el manejo de rincones en el aula de nivel inicial con niños y niñas de 3 a 5 años - Criollo Criollo, Mayra Silvana (2015)
The present study was performed in order to design a guide for the implementation of educational places for children aged between 3 and 5 years of age, considering that are important resource to implement significant strategies for building knowledge. A documentary literature study whereby information on the characteristics of children's cognitive, physical motor, social-emotional and language level was collected was performed. It was also investigated in the concept and features of the corners of classroom and on pedagogical rationale behind this practice. Finally the early education curriculum addressed to determine the curriculum framework, learning and development axes, output profile and role of the teacher. It was concluded that it is necessary, in schools where it is not have this resource, implement pedagogical corners in the classroom to work with children aged between 3 and 5 years, from the physical organization of space and basic materials which can be input from the school and parents. The guide includes a description of the most relevant pedagogical activities nooks and forth to illustrate its use.